Spatial mapping of photovoltage and light-induced displacement of on-chip coupled piezo/photodiodes by Kelvin probe force microscopy under modulated illumination - Eftekhari, Zeinab; Rezaei, Nasim; Stokkel, Hidde; Zheng, Jian-Yao; Cerreta, Andrea; Hermes, Ilka; Nguyen, Minh; Rijnders, Guus; Saive, Rebecca (Beilstein Journal of Nanotechnology, 2023)
In this work, a silicon photodiode integrated with a piezoelectric membrane is studied by Kelvin probe force microscopy (KPFM) under modulated illumination. Time-dependent KPFM enables simultaneous quantification of the surface photovoltage generated by the photodiode as well as the resulting mechanical oscillation of the piezoelectric membrane with vertical atomic resolution in real-time. This technique offers the opportunity to measure concurrently the optoelectronic and mechanical response of the device at the nanoscale. Furthermore, time-dependent atomic force microscopy (AFM) was employed to spatially map voltage-induced oscillation of various sizes of piezoelectric membranes without the photodiode to investigate their position- and size-dependent displacement.
Keywords: Kelvin probe force microscopy (KPFM); light-driven micro/nano systems; piezoelectric membrane; surface photovoltage (SPV); time-dependent AFM